2023
DOI: 10.20874/2071-0437-2023-60-1-1
|View full text |Cite
|
Sign up to set email alerts
|

New data on the formation of local variations in the Upper Paleolithic of the Caucasus

Abstract: As of today, very few Upper Paleolithic sites are known on both the southern and the northern slopes of the Caucasus. Their materials allow tracing settlement dynamics in the region from 40/39 to 20 cal ka BP. The change of the research methodology, which today is focused on thorough excavations involving a range of natural science disciplines for complex investigation of the materials, including complete water sieving of the cultural de-posits, enables obtaining many new, often unique data on human occupation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In the Caucasus, including the North Caucasus, the state of studies on the Middle Palaeolithic period differs significantly between the western and eastern half of this region [7][8][9]. Research of the last five years confirmed the previous assumption [10] that two culturally distinct populations of MP Neanderthals, which had different origins and traditions of stone-knapping and tool-making, inhabited the North Caucasus from at least late MIS 5 to mid MIS 3.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In the Caucasus, including the North Caucasus, the state of studies on the Middle Palaeolithic period differs significantly between the western and eastern half of this region [7][8][9]. Research of the last five years confirmed the previous assumption [10] that two culturally distinct populations of MP Neanderthals, which had different origins and traditions of stone-knapping and tool-making, inhabited the North Caucasus from at least late MIS 5 to mid MIS 3.…”
Section: Discussionmentioning
confidence: 72%
“…Layer 14 may be also correlated with late MIS 5, while the lower layers 15-23 have an older age, but rare lithic artefacts containing no diagnostic Mousterian tools were found in these Both the Levallois/laminar technology and the absence of bifacial tools typical for Eastern Micoquian distinguish the MP assemblages from Weasel cave from the Eastern Micoquian assemblages of the north-western Caucasus. Earlier, Golovanova and Doronichev [8,10] noted a particular similarity of MP assemblages from Weasel cave (especially from layers 12-14, dating from MIS 5) with the Zagros Mousterian industry in the Lesser Caucasus and Armenian Highlands [7] (Data 11 in S1 Text). The features that make the MP assemblages from the Weasel cave similar to Zagros Mousterian are the Levallois/laminar technology and the tool set that includes tool types typical for Zagros Mousterian assemblages in the Lesser Caucasus and Armenian Highlands (Fig 6; Data 12 in S1 Text).…”
Section: Plos Onementioning
confidence: 91%
See 2 more Smart Citations